Qualidade ambiental urbana em cidades médias: o setor leste em Uberlândia-MG - Santos, Gabriela Seabra (2020)
Based on studies on the Sustainable Project for the City (VITAL, 2012), and Environmental Design (FRANCO, 1997), the concept of Urban Environmental Quality seeks to meet the needs and expectations of contemporary man in balance with nature. The objective of this research is to assess the degree of Urban Environmental Quality in structural road systems in medium-sized cities through indicators as a tool capable of qualifying and verifying whether the urban interventions proposed in the road system correspond to the needs and expectations of the population. The proposed indicators are based on studies by Vital (2012) on the Sustainable Project for the City and Franco (1997, 2001) on Environmental Design and Environmental Planning. The methodology adopted for this reading is called Complex Unit Diagram – DUC –, organized by Vital (2012), and is divided into four dimensions: philosophical, environmental, built environment and urban web. The discussion on the Urban Environmental Quality of these avenues is an opportunity to verify whether the guidelines that underlie the execution of urban redevelopment projects of the road system in medium-sized cities, such as the case of the city of Uberlândia-MG, are in accordance with the needs and expectations of the population and sustainable development. Therefore, the result of this research is the evaluation of the Urban Environmental Quality degree of Segismundo Pereira and Anselmo Alves dos Santos avenues in Uberlândia-MG through the proposed indicators